2021
DOI: 10.1177/0969733020981761
|View full text |Cite
|
Sign up to set email alerts
|

Identifying ethical and legal issues in elder care

Abstract: Background: As a non–European Union member state, Albania is increasingly orienting itself on Western models regarding human rights, patient rights, and legal regulations for healthcare. Due to its limited fiscal and legal power, enforcing legal and ethical regulations poses a major problem. Aim: The aim of this study is to investigate nurse’s knowledge and experiences regarding ethical and legal issues in Albanian elder care in state-funded and privately run institutions. Research design: The study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Any issues were resolved by personal discussion and validation within the research team. Furthermore, the professional experience of the first and second authors as nurses and their cultural familiarity with the research participants improved the validity of the research method and results [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Any issues were resolved by personal discussion and validation within the research team. Furthermore, the professional experience of the first and second authors as nurses and their cultural familiarity with the research participants improved the validity of the research method and results [8].…”
Section: Discussionmentioning
confidence: 99%
“…An explorative qualitative research design was selected for the study. Data were collected through semi-structured interviews and field notes [8]. These interviews focus on considering the participants in their working environment and considering the researcher's observations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care professionals play a significant role in combating this health problem, particularly when patients suffer from severe symptoms that require hospital admission for treatment or even palliative care, as the main providers of end‐of‐life care. Several studies have demonstrated that nurses and nurse‐assistants experience pressure, burden, and emotional challenges concerning an increase in patient deaths (Hanna et al, 2021a , 2021b ; Podgorica, Flatscher‐Thöni, et al, 2021 ; Podgorica, Pjetri, et al, 2021 ; Podgorica, Shabani, et al, 2022 ) and insufficient resources to provide care (Mehta et al, 2021 ; Podgorica, Shabani, et al, 2022 ; Podgorica, Zenzmaier, et al, 2022 ). Previous studies focused on emotional and psychological distress that affected health care professionals' well‐being (Huang et al, 2020 , 2021 ; Mitchinson et al, 2021 ; Rathnayake et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%